RESPONSE OF CUCUMBERS TO DIFFERENT IRRIGATION REGIMES APPLIED THROUGH DRIP-IRRIGATION SYSTEM - U. Sahin; Y. Kuslu; F. M. Kiziloglu (Journal of Animal and Plant Sciences, 2015)
In the future, irrigated crop production will be affected significantly with water scarcity. There is a pressing need to improve the irrigation water efficiency under insufficient water supply conditions. Therefore, the effects of different irrigation quantities on the fruit yield, yield components (fruit length, diameter, weight and number), irrigation water use efficiency (IWUE) andfruit quality (minerals,phenolic content and antioxidant activity) ofdrip-irrigated cucumberwere evaluated in open field conditions. Different irrigation levels were adjusted usingthree different ratios(T1: 1.0, T2: 0.85 and T3: 0.70)of cumulative evaporation from a Class A pan.The maximumtotal fruit yield, early fruit yield, fruit length, fruit number per plant were determined fromT1 irrigation level(64.13 Mg ha-1, 2.76 Mg ha-1, 15.95 cm and 19.94), respectively.Significant positive linear relations were obtained between total fruit yield, fruit length and fruit number with irrigation quantity.The highest IWUE was obtained fromT2 irrigation level(134.94 kg ha-1 mm-1), however, there wasno significant difference among the treatments.The mineral content (N, K, Ca, Mg, S, Mn and Zn) and total antioxidant activity in cucumber fruits was higher in T2 irrigation level compared with the T1 irrigation level, the T1 irrigation level provided statistically higher total phenolic, Cu and B content compared withT2 and T3.In conclusion, the T1 treatment is recommended in semi-arid areas with acool climate for obtaining higher fruit yield. However, the T2 treatment is also recommended for obtaining higher IWUE and fruit quality if water is scarce.
Keywords: Cucumber; water-yield relationship; irrigation water use efficiency; total phenolics; antioxidant activity; mineral content